Synthesis and antidiabetic activity of β-acetamido ketones - Xing-hua Zhang; Ju-fang Yan; Li Fan; Gong-bao Wang; Da-cheng Yang (Elsevier, 2011)
This paper reports the use of trifluoroacetic acid as a catalyst in the Dakin-West reaction for the synthesis of β-acetamido ketones. The method has several advantages such as requiring only mild conditions and a low concentration of catalyst. Screening of 19 β-acetamido ketones for antidiabetic activity in vitro showed that their activity as peroxisome proliferator-activated receptor (PPAR) agonists and as dipeptidyl peptidase 4 (DPP-IV) inhibitors was fairly weak.